2010
DOI: 10.1007/s00403-010-1063-2
|View full text |Cite
|
Sign up to set email alerts
|

Does stereochemistry influence transdermal permeation of flurbiprofen through the rat skin?

Abstract: The possible enantioselectivity in the permeation of the chiral anti-inflammatory drug flurbiprofen across hairless rat skin was studied. The transdermal permeability of individual enantiomers from donor solution containing racemic flurbiprofen (0.1%) and pure enantiomers (0.05%) in isopropyl myristate solution was determined using side-by-side diffusion cells. The permeation profiles of enantiomers (R)- and (S)-flurbiprofen from donor solution containing racemic (RS)-flurbiprofen are comparable. When donor so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In this study, the superior skin permeability profile, including the favorable values of Q, Flux and lag time, of SFP as compared to FP in the YMP skin indicates the favorable physiological properties of SFP for percutaneous absorption. On the contrary, in a previous study carried out using hairless rat skin, the skin permeability profile of RFP was shown to be significantly superior to that of SFP [17]. This discrepancy could possibly be explained by the differences in the skin characteristics between YMP and rats.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, the superior skin permeability profile, including the favorable values of Q, Flux and lag time, of SFP as compared to FP in the YMP skin indicates the favorable physiological properties of SFP for percutaneous absorption. On the contrary, in a previous study carried out using hairless rat skin, the skin permeability profile of RFP was shown to be significantly superior to that of SFP [17]. This discrepancy could possibly be explained by the differences in the skin characteristics between YMP and rats.…”
Section: Discussionmentioning
confidence: 60%
“…The fact that the CNV-NLX (6) consists of a diastereomeric mixture may also be a matter of concern. Thus, the fact that stereochemistry has been shown to play a role in physiologic distribution, 9 combined with the likelihood that different preparations (batches), even from the same laboratory, may contain different percentages of each diastereomer, could compromise reproducibility and lead to misleading conclusions. This potential problem could be addressed by using single diastereomers of 6, which would best be separated at the ester precursor stage (5), or by using a single stereoisomer of the caging group, which would then produce a single diastereomer of the caged ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Transdermal preparation of FP can avoid the side effects of oral preparations, such as nausea, vomiting and peptic ulcers. It has been reported that enantioselectivity interaction was existed during transdermal permeation of FP across the rat skin (Valentov a et al, 2010), the steady-state flux and permeability coefficient of R-FP were significantly higher than those of S-FP. However, the permeation difference between racemate and enantiomers of FP has not been reported so far.…”
Section: Introductionmentioning
confidence: 87%
“…However, some other researchers reported that no enantiomeric differences existed in the permeation of propranolol through human skin (Heard et al 1993). Valentova et al has discussed the enantioselectivity of FP through rat skin, however, no FP enantiomers selectivity had been found through rabbit skin in the same report (Valentov a et al, 2010). Therefore, it is assumed that the discrepancy in the previous literatures could be attributed to the different kinds and amounts of CERs which contained in the skin of different species.…”
Section: In Vitro Permeation Studymentioning
confidence: 95%